Enterprise Architecture Design of Indonesian Engineers Association Using The Open Group Architecture Framework (TOGAF) - Qiqi Asmara, Abdullah; Firmansyah, Gerry; Tjahjono, Budi; Mulyo Widodo, Agung; Yudha Putra Hadjarati, Panji Ramadhan (Green Publisher Indonesia, 2024)
The Indonesia Engineers Association has used Microsoft Dynamics Axapta (AX) enterprise resource planning (ERP) software as its operational support system. However, there are obstacles that are obstacles to completing business processes effectively by users, which have an impact on declining work performance and not achieving company targets. In addition, for the next 3 years, IT solutions are also needed to be able to support business development in the company. The implementation of Enterprise Architecture is expected to be the answer for the Indonesia Engineers Association in the next 3 years, so that the company can be more productive and develop as well as there is alignment between the business strategies owned by the company to optimize the use of information systems and information technology owned by the Indonesia Engineers Association. The basis for choosing using the TOGAF ADM method in designing Enterprise Architecture is that TOGAF ADM has a complete methodology, clear and structured stages, so that the design and specifications become easier and reduce the implementation risks faced by the Indonesia Engineers Association. This research is expected to provide insights for policymakers and enterprise architecture practitioners in selecting and implementing the framework that best suits the context and needs of their organizations. In addition, this study also provides recommendations to improve the efficiency and effectiveness of the implementation of enterprise architecture in the Indonesia Engineers Association.